Agro Industries 4.0: Lessons from Japan to Colombia in rice production (2022)
Industry 4.0 is very relevant in today’s technological world, being its broadest application in countries with greater development, becoming a significant pillar in the search for growth in processes. Within agriculture, industry 4.0 has gained weight and has been more present in crop processes, improving production efficiency than it has been with rice production. In Japan, the production of this is highly promoted in the search for new technologies to increase the efficiency of the process, giving us greater production of rice per hectare, the opposite being the one that can be observed in Colombia. This article makes an analysis of the conditions of both countries for a transfer of technologies between them, speaking not only of material conditions, but also of history and social conditions.